Modelling and simulating self-organizing agent-based manufacturing systems - Barbosa, José (2010)
The multi-agent systems paradigm, enhanced with biological inspired concepts, such as swarm intelligence and selforganization, offers an alternative way to design control solutions that address the current demands or flexible, robust, responsive and adaptive manufacturing and automation systems. Being the development of these systems traditionally complex, the use of modelling and simulating environments may contribute for the fast prototyping and proof of concept of these solutions. This paper explores the use of these environments and uses the NetLogo platform to illustrate the development of an agent-based control application for an experimental production system. The designed and tested agent-based system exhibits robustness and adaptation to changing environments based on the stigmergy concept.